THE INTERSECTION OF WATER POLICY AND TECHNOLOGY: SOLAR INNOVATIONS FOR SUSTAINABLE AGRICULTURE IN ABSHERON PENINSULA OF THE AZERBAIJAN REPUBLIC (Eurasian Journal of Ecology, 2025)
This paper investigates the multifaceted challenges of water scarcity and sustainable agricultural development in arid and semi-arid regions, using the Absheron Peninsula as a case study. Emphasizing the critical role of renewable energy integration, the research explores how solar-powered technologies—ranging from solar treatment systems to photovoltaic-driven irrigation—can revolutionize water resource management for agricultural purposes. A 12-month empirical study, employing high-precision solar radiation measurements and advanced statistical analyses, reveals significant seasonal variability in solar energy availability and its synchronicity with agricultural water demands.The study synthesizes data on solar energy yields, system efficiencies, and temperature correlations to evaluate the feasibility of solar-powered solutions. By correlating solar energy availability with regional irrigation requirements, the research underscores the operational viability of technologies such as desalination, filtration, and UV disinfection in addressing seasonal water scarcity. Furthermore, the integration of sustainability metrics, including energy return on investment (EROI) and carbon offset potential, highlights the broader environmental and economic benefits of adopting solar-powered systems. This work also delves into the intersection of policy and technology, arguing for the alignment of innovative water policies with renewable energy frameworks to ensure long-term sustainability. The findings provide actionable insights for policymakers, engineers, and agricultural practitioners, advocating for scalable, adaptable solutions that enhance food security, minimize dependency on non-renewable resources, and foster climate resilience. By situating these innovations within the context of global sustainability goals, the study offers a replicable model for integrating renewable energy into agricultural water management, with implications for similarly resource-constrained regions worldwide.Keywords: Solar-powered technologies, water scarcity, solar irrigation systems, photovoltaic energy, agricultural sustainability